Peran Kepemimpinan Transformatif dalam Optimalisasi Manajemen Sumber Daya Manusia Pendidikan Islam. - Noviami, Rizki Raharyu; Sunhaji, Sunhaji (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the role of transformational leadership in optimizing human resource (HR) management in Islamic educational institutions. The main issue examined is how transformational leadership style, with inspirational, motivational, and spiritually-based characteristics, can contribute to the effectiveness of HR management systems in Islamic education, which have so far tended to be administrative and less strategic. This study uses a qualitative method with a literature study approach, analyzing various literature from 2020-2025 and previous research related to leadership, HR management, and Islamic values in education. The research results indicate that transformational leadership plays a significant role in improving teacher performance, building a collaborative and innovative work culture, and strengthening the integration of Islamic values in every aspect of human resource management. Additionally, transformational leadership can serve as an effective model for realizing adaptive, innovative, and quality-oriented HR management. This study recommends that future research develop an empirical model that examines the relationship between dimensions of transformational leadership and HR performance indicators in Islamic education across various types of institutions, such as madrasahs, pesantrens, and modern Islamic schools.